Alienasi Masyarakat Gambut: Dampak Program Pemberdayaan Masyarakat Terhadap Livelihood Masyarakat Desa Mantangai Hulu Kabupaten Kapuas - Ismar Hamid; Salsa Rizkia Meilinda (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
Increasingly massive damage to the peat ecosystem encourages the Indonesian government to tighten peat ecosystem management policies, as well as attracting the inclusion of various community empowerment programs based on peat ecosystem conservation. This research aims to describe a strategic approach to empowering peat communities, as well as the reality of the impact of the empowerment program on the livelihood of peat communities. This study uses a qualitative approach, with a case study type of research. The research location is in the village of Mantangai Hulu, District of Mantangai, Kapuas Regency, Central Kalimantan. Data collection was carried out through participant observation, in-depth interviews and documentation. Data were analyzed using Miles and Huberman's interactive model. The results of the research show that the community empowerment which is conducted in the village of Mantangai Hulu tends to apply a direct-action approach cum traditional. This approach has an impact on eliminating the livelihoods of local communities, which represents a reciprocal relationship with the peat ecosystem that takes place in harmony. There is also suppression of the existence of cultural values which is the identity of the people of the village of Mantangai Hulu. The consequence is that people are alienated from their own life on the peat ecosystem which has been going on for generations. The source of the problem is that the parties who do empowerment programs subjectively dominate the ideas of empowerment, and ignore the ecological knowledge that exists in peat community. As an antithesis, peat community empowerment must apply a transformative approach, whose climax point is marked by the community's ability to make decisions through the transformation of ecological thinking which is the guarantee for sustainable management of peat ecosystems.